2018
DOI: 10.1136/bcr-2018-225751
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response in osmotic demyelination syndrome presenting as severe parkinsonism, ptosis and gaze palsy

Abstract: Osmotic demyelination syndrome commonly affects the pons and infrequently involves the extrapontine region. We report a patient with severe hyponatraemia who developed osmotic demyelination syndrome as a consequence of rapid sodium correction. The condition manifested as acute severe parkinsonism, bilateral ptosis and gaze impairment. MRI revealed typical features of central pontine and extrapontine myelinolysis. The patient improved gradually after treatment with a combination of levodopa, intravenous immunog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, all these options need to be further studied to clarify their role in ODS management. Some patients with predominant dystonia and muscle rigidity showed a considerable response to levodopa 4 . Our patient received a low dose of carbidopa/levodopa.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…However, all these options need to be further studied to clarify their role in ODS management. Some patients with predominant dystonia and muscle rigidity showed a considerable response to levodopa 4 . Our patient received a low dose of carbidopa/levodopa.…”
Section: Discussionmentioning
confidence: 73%
“…Some patients with predominant dystonia and muscle rigidity showed a considerable response to levodopa. 4 Our patient received a low dose of carbidopa/levodopa. We appreciated an improvement in his clinical condition over more than four months of follow‐up.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Acute parkinsonism as a consequence of EPM may respond well to dopamine supply and immunotherapy. [11,21,22] Besides, previous studies have revealed that the volume of T2 signal change on MRI is not directly correlate with clinical outcome. [22]…”
Section: Discussionmentioning
confidence: 99%